THE ATTITUDE OF INFORMATION TECHNOLOGY STUDENTS IN MUTAH UNIVERSITY TOWARDS COMPUTERIZED EXAMS - Alnawaiseh, Asma; Alnawaiseh, Somaia (European Scientific Journal, ESJ, 2015)
The aim of this paper is to measure the attitude of Information Technology students in Mu’tah University towards computerized examination. In this study, we analyzed the following questions: Do students prefer computer based exams or paper based exam? Whatever their preference, why? What are the demographic factors that have affected the attitude of students towards computerized exams? We discussed the security concerns that come to light when considering computerized exams, such as: How can we secure computerized exams? Therefore, the data utilized in this paper was collected from questionnaires which were designed to achieve the stated objectives as well as to encourage a high response rate. The design of the questionnaires used in this paper mirrored those found in online international journals. We also, reviewed previous literature about students’ attitudes toward online tests. We obtained information about studentsâ€™ beliefs, attitudes, and feelings toward using computers in testing, adapting, and creating new items.